54th AIAA Aerospace Sciences Meeting 2016
DOI: 10.2514/6.2016-2026
|View full text |Cite
|
Sign up to set email alerts
|

Aero-Structural Design Optimization of Adaptive Shock Control Bumps

Abstract: Shock control bumps (SCB) are a transonic flow control device that aim to reduce the overall drag due to a normal shock on a typical passenger jet at cruise. The concept of adaptive SCB which can be deployed for best use are investigated through an aero-structural design tool that produces optimal geometries. The optimizer uses a surface based performance metric to highlight the importance of the flow quality around the SCB as well as including a structural element that is required to provide the necessary fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As mentioned before, Jinks et al [81,86] could keep the maximum von Mieses stresses below the limit of 90% yield stress. This is also true for the two-actuator solution in both actuation points [87].…”
Section: Thin Flexible Plate With Two Actuation Pointsmentioning
confidence: 87%
See 2 more Smart Citations
“…As mentioned before, Jinks et al [81,86] could keep the maximum von Mieses stresses below the limit of 90% yield stress. This is also true for the two-actuator solution in both actuation points [87].…”
Section: Thin Flexible Plate With Two Actuation Pointsmentioning
confidence: 87%
“…While in [81] (2015) the maximum stress in the single actuation point is approximately 69% of the yield stress, Jinks et al [86] (2016) could reduce this value to a reported 58% yield stress. Hence, in both approaches the stresses are far below 90% yield stress (safety factor: 10%) which the authors chose as limit.…”
Section: Actuated Thin Flexible Platementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies by Rhodes and Santer [25,26] showed numerically that morphing SCBs, which can be deployed through the actuation of a flexible membrane, are possible where designs have been generated that offer an optimum trade-off between structural, material, and aerodynamic constraints. Further, research from Jinks et al [27][28][29][30] demonstrated the efficacy of the morphing SCB experimentally and numerically in pre-buffet flows. A limitation of this technique is that under current materials technologies, the sharp geometries required for wedge-bumps (especially in 3D) are not feasible due to sharp corners, requiring large variations in Gaussian curvature over short distances, as well as the additional actuation required.…”
Section: Introductionmentioning
confidence: 98%
“…These methods can be broadly split into two groups: those which apply load directly to the aerofoil skin, and those which use topologically designed wing ribs to distribute an actuation load to the variable region. Applications where the actuation is applied directly to the skin include transonic shock control bumps (Jinks et al 2016) and stall prevention through an oscillating suction surface (Jones et al 2015). In these examples the variation in geometry is localised to the upper surface of the aerofoil, an area of low curvature, and the overall variation in geometry is small.…”
Section: Introductionmentioning
confidence: 99%